Komunikasi Politik Dewi Asmara dalam Kontestasi Pemilu Legislatif 2024 Di Dapil Jabar IV - Dindra Hasna Shabira (Jurnalika : Jurnal Ilmu Komunikasi, 2025)
This research attempts to describe Dewi Asmara's political communication in the 2024 Legislative Election Contestation in the West Java Regional Election District IV (Descriptive Study of Dewi Asmara's Political Campaign in Sukabumi City and Regency). This research describes the strategies and practices carried out by Dewi Asmara and her team in the 2024 Legislative Election contestation in the West Java IV electoral district. Based on the political communication theory by Kamarudin Hassan, political campaigns become systematic political media, seeks to create a specific place in the minds of audiences about the product, candidate, or idea being offered This research method is research that uses a qualitative approach Data collection was carried out through interviews, observations, and literature studies the informant withdrawal technique uses the selection of sources who are considered capable of representing the information as a whole. This research also describes the special strategy carried out by Dewi Asmara and her team to use mass media, public meetings and social media to convey messages to potential voters. The results of this research provide a deeper understanding of how Dewi Asmara and her team utilize their political communication to face the 2024 legislative election These findings provide valuable insight for practitioners of political communication in the context of Indonesian democracy. Further research could be conducted to see the impact of communication strategies on voter support and election results in 2024